Cell wall glycosylation in Staphylococcus aureus: targeting the tar glycosyltransferases. (June 2021) - Guo, Yinglan; Pfahler, Nina M; Völpel, Simon L; Stehle, Thilo
Highlights: Functional similarities and differences among S. aureus glycosyltransferases, TarM, TarS and TarP. Structural similarities and differences among S. aureus glycosyltransferases, TarM, TarS and TarP. The general strategies for interactions of WTA-processing enzymes with the repetitive WTA backbone. A structural motif in the poly-RboP binding domain harbors the base catalyst. Abstract : Peptidoglycan (PG) is the major structural polymer of the bacterial cell wall. The PG layer of gram-positive bacterial pathogens such as Staphylococcus aureus ( S. aureus ) is permeated with anionic glycopolymers known as wall teichoic acids (WTAs) and lipoteichoic acids (LTAs). In S. aureus, the WTA backbone typically consists of repeating ribitol-5-phosphate units, which are modified by enzymes that introduce glycosylation as well as amino acids at different locations. These modifications are key determinants of phage adhesion, bacterial biofilm formation and virulence of S. aureus . In this review, we examine differences in WTA structures in gram-positive bacteria, focusing in particular on three enzymes, TarM, TarS, and TarP that glycosylate the WTA of S. aureus at different locations. Infections with S. aureus pose an increasing threat to human health, particularly through the emergence of multidrug-resistant strains. Recently obtained structural information on TarM, TarS and TarP has helped to better understand the strategies used by S. aureus to establish resistance and to evade host defense mechanisms. Moreover, structures of complexes with poly-RboP and its analogs can serve as a platform for the development of new inhibitors that could form a basis for the development of antibiotic agents.